Trends and predictors of mortality among HIV positive patients in the era of highly active antiretroviral therapy in Uganda - John Rubaihayo; Nazarius M. Tumwesigye; Joseph Konde-Lule; Fredrick Makumbi; Edith J. Nakku; Henry Wamani; Michael B. Etukoit (MDPI AG, 2015)
Knowledge of mortality trends and predictors among HIV-positive patients in the era of highly active antiretroviral therapy (HAART) in resource poor settings is still limited. The aim of this study was to describe trends and predictors of mortality among HIV-positive patients in the era of HAART in Uganda. Data from 2004 to 2013 for adult HIV-positive patients (≥15 years) obtaining care and treatment from the AIDS Support Organization in Uganda were reviewed for mortality. Descriptive statistics were analyzed by frequencies and cross tabulations. Calendar period was used as a proxy measure for HAART exposure and a time plot of the proportion of HIV-positive patients reporting dead per year was used to describe the trends. Logistic regression was used to determine the predictors of mortality at bivariate and multivariate levels, respectively. We included in the analysis 95,857 HIV positive patients; 64% were female with median age of 33 years (interquartile range 27-40). Of these 36,133 (38%) were initiated on ART and a total of 4279 (4.5%) died; 19.5% (835/4279) of those who died had an opportunistic infection. Overall, mortality first increased between 2004 and 2006 and thereafter substantially declined (X2trend=211.9, P<0.001). Mortality was relatively higher in Eastern Uganda compared to other geographical areas. Male gender, older age (>45 years), being from Eastern or Northern Uganda, having none or primary education, being unemployed, advanced immunodeficiency (CD4 count <100 cell/μL or WHO stage III or IV) and underweight (<45 kg weight) at HAART initiation and calendar period 2004-2008 were significant predictors of mortality (P<0.001). Overall, the expanding coverage of HAART is associated with a declining trend in mortality among HIV positive patients in Uganda. However, mortality trends differed significantly by geographical area and men remain potentially at higher risk of death probably because of delayed initiation on ART. There is urgent need for men targeted interventions for improved ART performance.